Biochemical differences between distal limb extensor and flexor tendons among equine breeds selected for racing and sport. (August 2020) - Verkade, M.E.; Hazeleger, E.; van de Lest, C.H.A.; Back, W.
Highlights: Biochemical comparison of equine superficial digital flexor tendons and common digital extensor tendons. Thoroughbred racehorses and sports horses (Friesian and Warmblood horses) were compared. Sports horses had lower tendon collagen concentrations than Thoroughbreds, but higher water content and crosslink concentrations. Fibrillar collagen support predominates in Thoroughbreds; crosslink collagen support predominates in sports horses. The observed biochemical differences between breeds could be related to their intended locomotor performance. Abstract: Throughout the ages, humans have selected different horse breeds for their locomotor capacities. Consequently, the properties of equine locomotor tissues could have diversified because of the specific requirements of different disciplines. Therefore, this study aimed to compare biochemical properties of tendons in different equine breeds traditionally selected for racing or sports performance. We hypothesised that tendons in racing breeds would have biochemical properties that would increase strength, whereas those in sporting breeds would have more elastic properties. An ex vivo tendon tissue study comparing the common digital extensor tendon (CDET) and superficial digital flexor tendon (SDFT) of sports horses (Friesian horse, Warmblood horse) and racehorses (Thoroughbred horse; the oldest, reference standard breed) was performed. The SDFT and CDET from middle-aged Friesian ( n = 12), Warmblood ( n = 12) and Thoroughbred horses ( n = 8) were harvested, and their biochemical properties were compared. The biochemical analysis demonstrated significantly higher water percentage, lower collagen concentrations/glycosaminoglycan content and higher crosslink concentrations in the SDFT of sports horses compared to racing breed horses ( P < 0.05); DNA content was also significantly lower in sports horses than racehorses ( P < 0.05). Racehorses had mainly extra fibrillar collagen support, whereas sports horses had mainly extra crosslink collagen support. From a functional perspective, the racing Thoroughbred relied on stronger tendons, while the sporting Friesians and Warmbloods relied on less stiff, more elastic tendons. In conclusion, there were significant biochemical differences in tendon properties between breeds, possibly related to their intended locomotor performance, although this requires further biomechanical and ultimately genetic confirmation.